Sexual behaviour, human papillomavirus and its vaccine: a qualitative study of adolescents and parents in Andalusia - María González-Cano; Francisco Garrido-Peña; Eugenia Gil-Garcia; Marta Lima-Serrano; María Dolores Cano-Caballero (BMC, 2021)
Abstract Background Human papillomavirus (HPV) is one of the most common sexually transmitted infections and can be prevented by vaccination. The purpose of this study is to gain a better understanding, by analysing interview responses of adolescents and parents, of how adolescent sexual behaviour is approached in families, how widespread knowledge about HPV is in Andalusia, the autonomous region with the lowest vaccination rate in Spain, as well as to learn more about the interviewees' position regarding vaccination. Methods A qualitative study by means of 15 focus groups of adolescents (N = 137, aged 14-17 years) and five focus groups of parents with children of those ages (N = 37) was conducted in the provinces of Granada, Seville and Jaén (Andalusia, Spain). The audio data were transcribed verbatim, coded and analysed thematically using NVIVO-10 software. Results There were three major results: (1) There is a lack of communication between adolescents and parents regarding sexual behaviour; (2) In both groups, scarce knowledge about HPV and vaccination was found; (3) Parents mistrust vaccination due to a lack of qualified and verified information about its benefits. Conclusions Healthy adolescent sexual behaviour is aided by communication within the family. Families need more information based on the evidence about HPV and vaccination. Health professionals are a key element in this process.